Capital social et gouvernance des ressources naturelles collectives au Bushi dans le contexte post-conflit - Jules Barhalengehwa Basimine; Pascal Sanginga (VertigO)
This article examines how can the social capital be reinforce for enhancing beneficial collective action for governance of natural resources, especially wetlands and fields in Bushi region in the post conflict context. The paper reports results of action research project on governance of natural resources in the Kivu region of the Democratic Republic of Congo, a region that is emerging from armed conflicts. For collecting data, questionnaire surveys of 350 households, and some focus group interviews were conducted. Exploratory factor analysis has summarized the data to identify the dimensions of social capital with acceptable level of signification. While the reliability of the measurement scale was tested by Cronbach’s alpha, the results of the study show that in the order of priority, to strengthen social capital for the collective action of governance of natural resources in a post conflict context start by working systematically on social interaction between members of the villages and other social actors in the community. The second dimension which must be reinforced is the relationship between local associations and other forms of social organizations as the networks of governance of natural resource. The third dimension is the relationship between people and local authorities. Finally the strengthen of social conventions, norms and sanctions for good governance of natural resource.